Clinical importance of ischemic preconditioning [İskemik önkoşullamanin klinik önemi] - (:unkn) unknown (My University, 2012)
Ischemic preconditioning can be defined as the protective mechanism which is triggered against prolonged ischemia induced organ damage, by single or repetitive brief periods of ischemia-reperfusions. Since described for the first time in 1986 to date trials are made to reveal the mechanism and factors affecting the mechanism of ischemic preconditioning but experience is limited on clinical implication of ischemic preconditioning. In this paper, the effect of ischemic preconditioning on organs other than myocardium and its prominent effects in clinical practice are revealed.
Keywords: Clinical practice; Ischemia-reperfusion; Ischemic preconditioning